Ethical Values of Final Year Students at a Malaysian Private Higher Learning Institution - Khalid Ali, Khalidah (2012)
The deterioration of ethical values among the younger generation has been a great concern in the information and communication technology world of today. Despite the vast amount of knowledge available to educate humans on this Mother Earth, ethical problems are often highlighted, be it at home, learning institutions or the workplace. It is pertinent for a nation to ensure that the community emulates good ethical values while economic progress is promoted for general well-being. Malaysian schools and higher institutions of learning have continuously been offering ethics related courses to students as a national requirement. However, the extent of its impact remains to be significant. This paper assesses the level of ethics possessed by final year engineering and technology students at a private higher learning institution in Malaysia. In addition, comparisons have been made based on gender, nationality and religious background to examine whether there are differences in the students’ ethical level. A structured questionnaire was developed to measure three universally accepted moral values: Integrity, Self Control and Courage. The overall results showed that the students possessed moderate level of ethics from the above dimensions. The findings from the demographic perspective consistently showed that there is no significant difference in ethical values between male and female students, nationality and religion. The study had also provided an indication on the impact of ethics related subjects in shaping the moral values of students at this higher learning institution.